2017
DOI: 10.1097/aog.0000000000002136
|View full text |Cite
|
Sign up to set email alerts
|

Contraception After Delivery Among Publicly Insured Women in Texas

Abstract: Objective To assess women’s preferences for contraception after delivery, and to compare use with preferences. Methods In a prospective cohort study of women aged 18–44 years who wanted to delay childbearing for at least 2 years, we interviewed 1,700 participants from eight hospitals in Texas immediately postpartum and at 3 and 6 months after delivery. At 3 months, we assessed contraceptive preferences by asking what method women would like to be using at 6 months. We modeled preference for highly effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Requiring women to return to the clinic for financial screening on a different day often led to other barriers. Foreign‐born Hispanic women were more likely than U.S.‐born Hispanic women to experience a cost barrier, and previous research found that foreign‐born individuals were less likely than U.S.‐born ones to be relying on their desired IUD, implant or sterilization at six months postpartum . Thus, expanding public insurance coverage to immigrants, regardless of documentation status, as well as providing same‐day appointments for financial screening, could improve access to postpartum contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Requiring women to return to the clinic for financial screening on a different day often led to other barriers. Foreign‐born Hispanic women were more likely than U.S.‐born Hispanic women to experience a cost barrier, and previous research found that foreign‐born individuals were less likely than U.S.‐born ones to be relying on their desired IUD, implant or sterilization at six months postpartum . Thus, expanding public insurance coverage to immigrants, regardless of documentation status, as well as providing same‐day appointments for financial screening, could improve access to postpartum contraception.…”
Section: Discussionmentioning
confidence: 99%
“…wanted to be using a highly effective method at 6 months postpartum compared to 39% actually using one [31]. Among Texas community college students, 21% wanted to be using an IUD or implant, but less than half (9%) were [32].…”
Section: Measuring Access To Contraceptionmentioning
confidence: 99%
“…Even in high‐income countries, provision of effective contraception after delivery is often sub‐optimal. Only around 50% of postpartum women in a Texan study expressing a preference for either long‐acting reversible contraception (LARC) or sterilization received their preferred method . About 70% of pregnancies occurring within 1 year postpartum in the USA are unintended .…”
Section: Introductionmentioning
confidence: 99%